2004
DOI: 10.1007/s00439-004-1100-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel microsatellite markers and single nucleotide polymorphisms refine the tylosis with oesophageal cancer ( TOC ) minimal region on 17q25 to 42.5�kb: sequencing does not identify the causative gene

Abstract: Tylosis (focal non-epidermolytic palmoplantar keratoderma) is associated with the early onset of squamous cell oesophageal cancer in three families. Linkage and haplotype analyses have previously mapped the tylosis with oesophageal cancer ( TOC) locus to a 500-kb region on chromosome 17q25 that has also been implicated in sporadically occurring squamous cell oesophageal cancer. In the current study, 17 additional putative microsatellite markers were identified within this 500-kb region by using sequence data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Currently, a rare autosomal dominant disorder defined by a genetic abnormality on chromosome 17q25 is the only recognised familial syndrome that predisposes patients to squamous cell carcinoma of the oesophagus [36]. The present study has provided some modeling parameters of oesophageal cancer for further genetic linkage studies.…”
Section: Discussionmentioning
confidence: 89%
“…Currently, a rare autosomal dominant disorder defined by a genetic abnormality on chromosome 17q25 is the only recognised familial syndrome that predisposes patients to squamous cell carcinoma of the oesophagus [36]. The present study has provided some modeling parameters of oesophageal cancer for further genetic linkage studies.…”
Section: Discussionmentioning
confidence: 89%
“…Although CYGB is not mutated in tylotic individuals [31] or in a series of sporadic squamous cell oesophageal carcinomas [34], we have shown that its expression is strongly downregulated in non-cancerous oesophageal biopsies from patients with TOC compared with normal biopsies [33]. CYGB is also methylated and downregulated in sporadic oesophageal, lung and head and neck cancers [27], [28], [33].…”
Section: Introductionmentioning
confidence: 75%
“…35 Another example is CYGB expression, the fifth most important feature. CYGB shows variable expression in cancers: it is down-regulated in many cancers 36 but up-regulated in lung and brain metastases, and head and neck cancer. 37,38 The methylation level at a LAMA4 promoter CpG was found as the seventh most important feature; previously, the aberrant methylation at the LAMA4 promoter was observed in breast carcinoma 39 and low methylation was associated with poor progression-free survival.…”
Section: Resultsmentioning
confidence: 99%